Assessment and prediction of fire-dangerous seasons in the Left-Bank Forest Steppe by means of dendrochronological methods - Коваль , І. М.; Ворон , В. П.; Мельник , Є. Є.; Сидоренко , С. Г. (Forestry and Forest Melioration, 2022)
Introduction The study analyses the radial growth of Pinus sylvestris L. in the Left-Bank Forest-Steppe. The purpose of the work was to predict fire-hazardous seasons by means of dendrochronological methods based on the solar activity dynamics for the Left-Bank Forest-Steppe. Materials and Methods We selected pine cores from a 100-year-old pure pine stand that grows at the territory of the State Enterprise “Kharkiv Forest Research Station” and used standard dendrochronological methods as well as the superimposed epoch method. Thus, the research was based on a procedure of filtering a low-frequency component in multi-year growth fluctuations. The superimposed epoch method belongs to the non-parametric methods of identifying hidden periodicity. The essence of the method is that the analysis of the dynamics of tree growth and fluctuations of climatic factors is carried out within the 11-year cycle of solar activity, also known as the Schwabe-Wolf cycle. The advantage of this method is the absence of a priori assumption on the form of the periodic component, which in most cases is considered to be harmonic, and therefore, it allows determining a true form of the periodic component and forecasting dry and wet years. The multiple regression model of Wolf numbers and weather data of the Kharkiv weather station were used to forecast the dynamics of the radial growth of Scots pine. Results A regional chronology was created for the Forest-Steppe, consisting of 62 individual tree-ring series. The dynamics of the RESIDUAL tree-ring index chronology and the dynamics of Wolf numbers were compared. The solar activity cycles according to Wolf numbers with a duration of 9–13 years are 1823–1834, 1834–1843, 1843–1856, 1878–1889, 1889–1901, 1901–1912, 1912–1924, 1924–1934, 1934–1944, 1944–1954, 1954–1964, 1964–1976, 1976–1986, 1986–1997, 1997–2008, 2008–2019 and 2019–2030. On the branch of rising solar activity, there is an increase in precipitation and the amplitude of fluctuations in both humidity and temperature. Conclusions We came to the conclusion that there is a close relation between the indices of Selyaninov’s hydrothermal index and Wolf numbers on the one hand and radial growth indices on the other hand. The dendrochronological methods revealed the years with minimum moisture levels, i.e. the fire-dangerous years 2020, 2024 and 2028, as well as the years with maximum moisture levels: 2021, 2023 and 2025. The study showed that the highest temperatures are observed on the branch of increasing solar activity four years before the maximum Wolf numbers, as well as on the 4th year after the maximum Wolf numbers on the branch of the decline of solar activity, as well as in the year of the maximum solar activity. The lowest temperatures were established in the 1st and 3rd years on the branch of increasing solar activity, that is, before the maximum Wolf numbers, and on the branch of decreasing solar activity in the 1st and 3rd years after the maximum Wolf numbers. It is worth noting that wet periods should be used for creating forest stands, while transitional periods to dry years – for maintenance felling. 9 Figs., 2 Tables, 9 Refs.